การใช้ไซยานิดินที่สกัดจากกะหล่ำปลีม่วงเป็นสารตรวจวัดไอออนโลหะหนัก - แพรพลอย พรหมสวัสดิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
Heavy metal ions are harmful to the environment and life processes. For example, Cu can be toxic to biological systems when they exceed the levels of cellular needs and is also able to displace other metal ions which act as cofactors in enzyme-catalyzed reactions. In this work, we developed a simple method for detecting metal ions by using cyanidin extracted from red cabbage as a selective chelating agent that was investigated in terms of qualitative analysis. Cyanidin is one kind of anthocyanin that can be isolated from plants in its red-colored flavylium form. Cyanidin was extracted from red cabbage using the mixture of methanol and 2M hydrochloric acid (85:15 v/v) at room temperature to get a powdered cyanidin extract. Metal ions such as Al(III) Cu(II) and Fe(III) were used to test the change of color of cyanidin upon varying pH from 4 to 7. It was found that cyanidin changed color upon adding different metal ions. Masking agents such as potassium fluoride was used to improve the selectivity of the detection. It was found that potassium fluoride can mask Al(III) at pH 4. Moreover, we developed a simple method for the detection of Cu(II), Fe(III), and Al(III) using test strips. The test strips were moistened with cyanidin solution and then dried in the air. The result showed that the test strips could detect Fe(III).